Tinjauan Kelengkapan Pengisian Formulir Ringkasan Pasien Pulang Rawat Inap Pada Kasus Covid-19 di Rsud Tarakan Jakarta Tahun 2022 - Izmi Novianita; Wiwik Viatiningsih; Nanda Aula Rumana; Puteri Fannya (Pusat Riset dan Inovasi Nasional, 2023)
Medical records are an important part of reporting and recording as well as assisting the implementation of service delivery to patients, one of which is a summary form for discharge patients, which includes all services that have been provided to patients. It was found that there were still medical records that were not 100% complete according to service quality standards at the Tarakan Hospital, Jakarta. Researchers analyzed the medical records of inpatients for COVID-19 cases, especially the summary form for discharge patients. This study uses a descriptive method with a quantitative analysis approach. The purpose of this study was to determine standard operating procedures and calculate the percentage of completeness of inpatient medical records on the summary form of inpatient discharge patients in the case of covid-19 in March 2022, and to find out the obstacles in filling out the summary form of inpatient discharge in cases of covid-19 . Based on the results of a study of 152 medical records of hospitalized patients with COVID-19 cases, the average completeness rate was 92% complete and 8% incomplete. The need to resocialize standard operating procedures for filling out medical records and the need for hospital director decisions regarding the discipline of filling out medical records should be able to be carried out properly and on time .